(untitled) (EU and comparative law issues and challenges series (ECLIC), 2024)
EU competition law is one of the most important fields of the internal market’s development and a key aspect of the European economic integration. Indeed, free competition may be an important element of an open market economy, but its safeguarding through regulatory supervision and intervention has been a fundamental economic and political choice made quite early by the founders of the EEC Treaty. Despite decentralization of the enforcement system achieved by Regulation 1/2003, the Commission continues playing an important role in the enforcement of EU competition law. Nevertheless, , the exercise of its strengthened investigative powers is subject to EU fundamental rights, whose protection is embedded in the EU Charter of Fundamental Rights. Additionally, national competition authorities are also obliged to respect the same EU fundamental rights when enforcing EU law, as is provided by art. 51 Charter and settled case-law of the Court of Justice of the EU. The paper will aim at elucidating the limits of the legal and administrative enforcement of competition rules imposed by human rights, as well as the function of the EU judicial system in competition law, emphasizing the distinction between the partly limited review of legality of the Commission’s acts and the unlimited review of the amount of fines imposed. The ultimate goal is to measure the influence of the right to a fair trial in its efficiency.